Kryteria podziału rezerw zdolności produkcyjnych w przemyśle - Glinkowski, Czesław (Wydział Prawa i Administracji UAM, 1969)
The calculation of the optimalization of the exploitation of the productive ability can not be limited only to the determination of the total size of the reserves that appear in the examined element of production. For the size of these reserves is influenced by different factors and the accepted qualification of productive ability. In the paper it was accepted that the productive ability expresses the maximization of production taking into account optimum and not maximum of the conditions of production. The ability calculated on such a basis establishes a model based on real but not in every case workable factors in the realization. These factors are differentiated with appropriateness to the object for which the examination is done. The strength of action of individual factors and the possibility of quantifying and liquidating them are variable. Assuming what has been said about the notions and factors the reserves of productive ability do not have a homogeneous character. In the paper there were individualized some criteria of the classification of reserves. These criteria were connected with: — dynamic character of the productive ability calculated of the basis of optimal use of all the factors determining it in a unit of time; — two basic elements of the model of calculation of the productive ability namely the technical standard of the efficiency of work and the effective time of work; — suitableness of the prevalence of reserves; — analysing the use of productive ability at the level: productive ability — planned production — executed production. The criteria mentioned above allow to make acquaintance of the structure of reserves and they should have a great influence on better knowledge of the essence of ability and reserves of production and on the effectiveness of the economic enterprises. Especially they ought to make easier the planning and the realization of the organizational and technical enterprises directed towards rational delivering the reserves and stimulating the production.
Criteria of the Division of Reserves of the Productive Ability in Industry